Derecho a la salud, justicia sanitaria y globalización: un debate pendiente (2011)
ABSTRACT: This paper, as a theoretical review, presents an approach to the issue of the right to health within the framework of health justice in today’s globalization. To this end, some of the effects of globalization on people’s life and health conditions, as well as the increase in health inequalities, are initially shown. After this, in order to highlight some of the points in the debate, the schools of thought that have approached the issue of social justice and its effects on health systems from the standpoint of moral philosophy are reviewed. Next, it is proposed that the discourse of human rights and the right to health become, specifically, an idea —an important force linked to global health justice with potentialities and restrictions imposed by its own configuration process—. Finally, it is concluded that the discussion about the right to health, health inequities and health justice has to go beyond the national boundaries and start referring to international relationships. In this debate, public health, as a transdiscipline, must prioritize this issue in its theoretical, exploratory, and social praxis agenda.